PENGARUH KONSENTRASI ASAM HIALURONAT TERHADAP STABILITAS FISIK SALEP KOMBINASI EKSTRAK IKAN GABUS - Lelek Kipli; Mohamad Andrie; Wintari Taurina (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The combination of snakehead fish ointment is expected to have synergistic properties in wound healing. Variations in natural ingredients added to the formula will affect the stability of the preparation during its shelf life. Hyaluronic acid, as a humectant agent, is used to maintain stability and improve physical properties by increasing the consistency of the preparation and reducing the risk of syneresis. The test method in this study was the stability test of the intermediate at 30°C ± 2°C/ RH 65 ± 5 % for six months. The Parameters measured were spreadability, adhesion, and pH. The observations showed that all formulas met the physical characteristics of the ointment until the 1st month. The 0.25% hyaluronic acid concentration was the most stable formula, which maintained the stability of spreadability and adhesion up to the 1st-month test point.